EHRA expert consensus statement on the management of cardiovascular implantable electronic devices in patients nearing end of life or requesting withdrawal of therapy - Padeletti, Luigi; Arnar, David O.; Boncinelli, Lorenzo; Brachman, Johannes; Camm, John A.; Daubert, Jean Claude; Kassam, Sarah; Deliens, Luc; Glikson, Michael; Hayes, David; Israel, Carsten; Lampert, Rachel; et al. (Europace, 2010)
The purpose of this Consensus Statement is to focus on implantable cardioverter-defibrillator (ICD) deactivation in patients with irreversible or terminal illness. This statement summarizes the opinions of the Task Force members, convened by the European Heart Rhythm Association (EHRA) and the Heart Rhythm Society (HRS), based on ethical and legal principles, as well as their own clinical, scientific, and technical experience. It is directed to all healthcare professionals who treat patients with implanted ICDs, nearing end of life, in order to improve the patient dying process. This statement is not intended to recommend or promote device deactivation. Rather, the ultimate judgement regarding this procedure must be made by the patient (or in special conditions by his/her legal representative) after careful communication about the deactivation's consequences, respecting his/her autonomy and clarifying that he/she has a legal and ethical right to refuse it. Obviously, the physician asked to deactivate the ICD and the industry representative asked to assist can conscientiously object to and refuse to perform device deactivation.
Gesehen am 21.06.2023